Pengaruh Persepsi Kualitas Produk, Merek dan Layanan Purna Jual Terhadap Keputusan Pembelian Skuter Metik Merek Honda di Kota Banda Aceh - Jufidar Jufidar; Fakhrurrazi Abbas; Irwan Safwadi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
This research is an empirical study which aims to determine the effect of perceptions of product quality, brand and after-sales service on the decision to purchase Honda brand metic scooters in Banda Aceh City either partially or simultaneously. The number of research samples is 381 consumers. Sampling in this study was carried out with a minimum sample formulation using the Slovin method. Data collection is done by distributing question sheets (questionnaires) to respondents. The primary data is then analyzed using multiple linear regression. The results of multiple linear regression analysis can explain that the perception of product quality, brand and after-sales service has a positive effect on the purchase decision of Honda brand metic scooters in Banda Aceh City. The effect of the three variables is significant with a significant probability value <0.05. Or, simultaneously the perception of product quality, brand, and after-sales service has a strong and positive relationship with the decision to purchase Honda brand metic scooters in Banda Aceh City in Banda Aceh City. The role of perceptions of product quality, brand and after-sales service in influencing the decision to purchase Honda brand metic scooters in Banda Aceh is still less dominant with R2 of 0.386